REVIEW OF IOT SUBJECT: TREND AND CHALLENGE FOR RESEARCH AND PUBLICATION - Nadifa, Ulfatun; Mohamad, Yasin; Asmara, Bambang Panji; H, Haeriani; Ode Asri, Aristi Ayuningsi; Dongka, Rahmat Hidayat; Ashari, Sri Ayu; Saputra, Wahyu; Mutmainnah, Nur (Inverted: Journal of Information Technology Education, 2025)
The Internet of Things (IoT) has emerged as a transformative technology that is revolutionizing various industries and everyday life. This study aims to explore current trends and challenges in IoT research and publication. The research method employed in this study begins with a blind search across various international journal databases, followed by ranking the minimum and maximum percentages of each IoT subject. The journal databases used include IEEE, Science Direct, Taylor and Francis, and NATURE. Subjects with minimal rankings or IoT journal topics with the lowest percentages in each database were then reviewed based on predetermined filters. The blind search results revealed that IoT subjects with the lowest percentages were IoT Smart Farming at 0.87%, IoT Smart Bin at 1.54%, and IoT Smart Water at 2.73%. A review was subsequently conducted on journals covering IoT subjects to identify trends and challenges related to techniques, tools, and objects in the subjects with the lowest percentages.